Simplified dynamic analysis of high-rise buildings : applications to simplified seismic diagnosis and retrofit using the extended rod theory /: applications to simplified seismic diagnosis and retrofit using the extended rod theory. ([2019]) - Takabatake, Hideo
No abstract available